Association of chronic pain caused by endometriosis with the advent of bruxism (Research, Society and Development, 2022)
Bruxism is characterized as a repetition disorder, caused by the habit of involuntary grinding of the teeth. Such dysfunction is closely associated with psychological imbalances, being able to be related to chronic pain, arising from diseases such as endometriosis. The aim of this study is to analyze the correlations between bruxism and endometriosis. Through an integrative literature review, this study used the databases of the Virtual Health Library (BVS), Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature on Health Sciences (LILACS) and PubMed (National Library of Medicine). The Boolean operators “AND” and “OR” were used, with the health descriptors: Bruxism, Endometriosis, Chronic Pain, Pelvic Pain, Etiology, with the help of the Health Science Descriptors (DeCS). The inclusion criteria were: studies pertinent to the research, complete, free, in Portuguese and English, within the period from 2010 to 2022. The exclusion criteria were: studies that deviated from the theme, duplicates, simple and expanded abstracts, articles from opinion and reviews. With the search it was possible to find 112 articles, 47 were duplicates and 65 were excluded by quick reading, leaving 30 studies read in full, after that another 18 were eliminated, leaving 12 articles to compose this research. Through this research, it is concluded that bruxism has a high association with emotional state, together with the chronic pain of endometriosis, this can be a causative factor of bruxism, due to the chronicity and intensity of pelvic pain.